Analysis of Effective Promotional Media in Marketing Tour Package Products: A Case Study in Pangandaran Regency - Adiguna, Rido; Nurhayati, Atikah; Suryana, Asep Agus Handaka; Pamungkas, Wahyuniar; Prihadi, Donny Juliandri (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2024)
Purpose: This study aims to analyze effective promotional media for marketing tour package products in Pangandaran Regency. Method: The method used in this research is descriptive quantitative. The data got through survey data collection methods distributed to 40 respondents with a purposive sampling technique. The respondents are 40 people who have bought tour packages for Pangandaran or who have visited Pangandaran.Then the data from the 40 respondents were processed using SPSS analysis tools with descriptive statistical analysis techniques. Result: Based on the results of data analysis got using the SPSS analysis tool, the effective promotional media in marketing tour package products in Pangandaran Regency is social media with an average score of 4.70 respondents' answers including in the very high category and the type of social media is the Instagram application with an average score of 4.83 respondents answers including in the very high category. Contribution: The results can be a reference for travel agents or the like in promoting tour package products.